Introducing the Dilation and Evacuation Technique in Brazil: Lessons Learned From an International Partnership to Expand Options for Brazilian Women and Girls - Stifani, Bianca M.; Mei Hwang, Susane; Rodrigues Catani, Renata; Borges Martins da Silva Paro, Helena; Benfield, Nerys (Frontiers in Global Women's Health, 2022)
Dilation and evacuation (D&E) is the recommended surgical procedure for uterine evacuation in the second trimester. Despite its established safety record, it is not routinely available in most countries around the world. In this paper, we describe the multi-phase capacity-building project we undertook to introduce D&E as an option for Brazilian women and girls. First, we invited a highly motivated obstetrician-gynecologist and abortion provider to complete an observership at an established D&E site in the United States. We then organized a month-long focused clinical training for two experienced gynecologists in Brazil, followed by ongoing remote mentorship and support. Despite the restrictive legal setting and prevailing abortion stigma in Brazil, our training was well received, and we did not experience any overt resistance or hostility from physicians or other staff. We learned that obtaining institutional support is essential; and that presenting scientific evidence during dedicated didactic times was an important strategy to obtain buy-in from other local healthcare providers. An important challenge we encountered was low case volume given the restrictive legal setting. We addressed this by partnering with nearby hospitals and nonprofit organizations for patient referrals. We also rescheduled, adapted and optimized this project for implementation in the midst of the COVID-19 pandemic. Despite the challenges we faced, this project led to the successful introduction of D&E up to 16 weeks at two sites in Brazil. In the future, we plan additional training to increase capacity for D&E at more advanced gestational ages.